Flame-retardant biaxially oriented polyamide film and preparation method thereof

By adopting multi-layer flame retardant design and collaboratively prepared flame retardant units in BOPA films, combined with the use of molecular chain growth agents, the problem of insufficient flame retardancy and tensile strength in lithium batteries and electronic products packaging is solved, and efficient flame retardant performance and excellent mechanical properties are achieved, while avoiding the generation of toxic smoke.

CN119502515AActive Publication Date: 2025-02-25XIAMEN CHANGSU IND CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411528995.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-25
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

The existing BOPA films cannot meet safety requirements due to insufficient flame retardancy and insufficient tensile strength in lithium batteries and electronic products packaging. At the same time, traditional halogen flame retardants will produce toxic smoke during combustion.

Method used

A multi-layer flame retardant design is adopted, including a flame retardant upper surface layer, a flame retardant polyamide core layer and a flame retardant lower surface layer. A flame retardant unit is prepared by a collaboratively prepared by active dicarboxylic acid phosphine oxide flame retardant monomer, polyhydroxyphosphonate and 9,10-dihydro-9-oxa-10-phosphophenophenoxide, and a molecular chain growth agent is added during the polymerization process to improve the viscosity and mechanical properties of the material.

Benefits of technology

The high flame retardant bidirectional tensile polyamide film is achieved with high flame retardant performance and excellent tensile strength, which can meet the safety needs of lithium-ion batteries and electronic product packaging, while avoiding the toxic smoke problem of halogen flame retardants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119502515A_ABST
    Figure CN119502515A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of flexible packaging of polyamide films, in particular to a flame-retardant biaxially oriented polyamide film and a preparation method thereof. The polyamide film is sequentially composed of an upper flame-retardant surface layer, a flame-retardant polyamide core layer and a lower flame-retardant surface layer from top to bottom. The flame-retardant upper surface layer is prepared from the following components in parts by mass: 1 to 10 parts of anti-sticking master batch and 90 to 99 parts of flame-retardant nylon composite material; the flame-retardant polyamide core layer is prepared from 1 to 15 parts of 3-ethylidene bis (ethyl phosphinic acid) aluminum salt and 85 to 99 parts of a flame-retardant nylon composite material; the flame-retardant lower surface layer comprises 1-10 parts of anti-sticking master batch and 90-99 parts of a flame-retardant nylon composite material. The flame-retardant biaxially oriented polyamide film provided by the invention has the advantages of good flame retardant property, excellent mechanical properties, environmental protection and no pollution, and is especially suitable for the field of electronic product packaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of film flexible packaging, and in particular to a flame-retardant biaxially oriented polyamide film and a preparation method thereof. Background Art

[0002] BOPA film, or biaxially oriented nylon film, is one of the three most popular films. In addition to its high tensile strength and excellent puncture resistance, it also has outstanding gas barrier properties, pinhole resistance, transparency, and printability. It can meet people's requirements for packaging materials with high barrier properties, high strength, high transparency, thinness, lightness, and a very wide temperature range (-60℃~150℃). Therefore, it is widely used in many packaging fields such as food packaging, pharmaceutical packaging, cosmetic packaging, and mechanical and electronic product packaging.

[0003] With the continuous development of social economy, the application of BOPA film in other new fields has also been developed, such as aluminum-plastic packaging film for lithium batteries and electronic product packaging. Lithium batteries and electronic products may have the risk of spontaneous combustion or explosion, or even fire during use. Therefore, the nylon film used for packaging of such products also needs to have good flame retardant ability, but the flame retardant grade of nylon material itself is not high, only reaching UL94 V-2, and the oxygen index is about 24, which does not meet the application standards of lithium batteries and electronic products.

[0004] In the prior art, halogen flame retardants are often used to improve the flame retardancy of BOPA films. However, halogen flame retardants will produce a large amount of corrosive smoke and toxic gases during combustion, which will not only pollute the environment, but also threaten the safety of life and property.

[0005] In addition, since lithium batteries and other battery products are prone to bulging and deformation, the tensile strength of their packaging is particularly important. Once lithium batteries and other battery products bulge or deform, resulting in damage to the packaging, it will cause safety hazards. In order to increase the flame retardancy of general flame retardant films, inorganic flame retardants, halogen flame retardants, etc. are usually used. For example, CN 116100895 A discloses a flame retardant matte polyamide film. However, these existing flame retardants cannot meet the requirements of biaxial tensile strength of lithium batteries and other battery products when added to BOPA films. Some flame retardants even reduce their biaxial tensile strength, making their safety impossible to guarantee. Summary of the invention In order to solve the problem that a biaxially stretched polyamide film has both flame retardancy and biaxial tensile strength, the present invention provides a flame retardant biaxially stretched polyamide film, wherein the film is composed of a flame retardant upper surface layer, a flame retardant polyamide core layer and a flame retardant lower surface layer from top to bottom; By mass: The flame retardant upper surface layer comprises 1 to 10 parts of anti-sticking masterbatch and 90 to 99 parts of flame retardant nylon composite material; The flame retardant polyamide core layer comprises 1 to 15 parts of 3-ethylenebis(ethylphosphinate) aluminum salt and 85 to 99 parts of a flame retardant nylon composite material; The flame retardant lower surface layer comprises 1 to 10 parts of anti-sticking masterbatch and 90 to 99 parts of flame retardant nylon composite material; The flame retardant nylon composite material is polymerized by caprolactam, purified water, flame retardant unit, glacial acetic acid and molecular chain extender in a mass ratio of 62-89.8:5-10:5-20:0.1-3:0.1-5.

[0006] In one embodiment, the flame retardant unit is prepared by compounding an active dicarboxylic acid phosphine oxide flame retardant monomer, polyhydroxyphosphonate and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-propionic acid methyl ester 10-oxide in a mass ratio of 20-40:30-50:10-50.

[0007] In one embodiment, the polymerization of the flame retardant nylon composite material comprises the following steps: Add caprolactam, purified water, flame retardant unit, glacial acetic acid and molecular chain extender into a high-pressure reactor, evacuate for 10 to 120 minutes, introduce nitrogen for 5 to 40 minutes, and circulate 3 to 10 times to ensure that each component is under nitrogen protection conditions, and control the pressure in the high-pressure reactor to maintain at 0.1 to 1.5 MPa; Heat the autoclave to 50-100°C and start stirring at the same time. The stirring speed is controlled at 20-150r / min and kept under this condition for 1-10 hours to ensure that it is completely melted and becomes a uniformly mixed fluid; The high-pressure reactor is heated to 210-290°C and reacted under this condition for 2-24 hours, and the pressure is reduced to normal pressure by venting, and the temperature is reduced to 30-100°C to obtain a polymer; The polymer is discharged, pelletized through a casting belt, dried at 80-120° C. and the moisture content is controlled to be less than 600 ppm to obtain the desired flame-retardant nylon composite material.

[0008] In one embodiment, the dicarboxylic acid phosphine oxide flame retardant monomer is a substance comprising the following structure: ; The polyhydroxyphosphonate is a substance comprising the following structure: ; The 9,10-dihydro-9-oxa-10-phosphaphenanthrene oxide is a substance comprising the following structure: or .

[0009] In one embodiment, the particle size D of the aluminum salt of 3-ethylenebis(ethylphosphinate) is 50 ≤1.2μm, particle size D 95 ≤3.0μm, phosphorus content of aluminum salt ≥23%.

[0010] In one embodiment, the anti-sticking masterbatch is composed of polyamide 6 and / or a lubricant and / or an anti-blocking agent and / or an antioxidant and / or a nucleating agent.

[0011] In one embodiment, the anti-sticking masterbatch is composed of 70-91.6 parts of polyamide 6, 3-10 parts of lubricant, 5-15 parts of anti-blocking agent, 0.3-3 parts of antioxidant and 0.1-2 parts of nucleating agent by weight.

[0012] In one embodiment, the lubricant is selected from any one of oleamide, erucic acid amide, ethylene bislauramide, stearamide, silicone powder, ethylene bisoleamide, ethylene bisstearamide, or a mixture of at least two of them in any proportion; The opening agent is selected from any one of silicone resin, magnesium carbonate, aluminum oxide, talc, silicon dioxide, calcium carbonate, titanium dioxide, kaolin, barium carbonate, diatomaceous earth, or a mixture of at least two of them in any proportion; The antioxidant is selected from any one of antioxidant 1010, antioxidant 1098, antioxidant 168, antioxidant SEED, and antioxidant DNP, or a mixture of at least two of them in any proportion; The nucleating agent is selected from any one of caprolactam cyclic dimer and 2,2′-methylene-bis-(4,6-di-tert-butylphenyl) phosphate sodium salt or a mixture of at least two of them in any proportion; The molecular chain extender is 1,2-cyclohexanediol diglycidyl ether.

[0013] In one embodiment, the thickness of the polyamide film is 10 to 50 μm; The thickness of the flame retardant upper surface layer and the flame retardant lower surface layer are both 1-4 μm; the thickness of the flame retardant polyamide core layer is 2-48 μm.

[0014] The present invention also provides a method for preparing any of the flame-retardant biaxially oriented polyamide films as described above, comprising the following steps: S100, polyamide 6 and / or lubricant and / or opening agent and / or antioxidant and / or nucleating agent are mixed in a high-speed mixer according to a set ratio, melt blended, extruded, stretched and pelletized by a twin-screw extruder to obtain the desired anti-sticking masterbatch, and dried for use; Among them, the extruder temperature is 225 ~ 275 ℃, the drying temperature is 70 ~ 100 ℃, and the moisture content of the final anti-sticking masterbatch is less than 800ppm; S200, mixing the flame-retardant nylon composite material and 3-ethylenebis(ethylphosphinate)aluminum salt according to a set ratio, and putting them into a high-speed mixer for uniform mixing to make them dispersed evenly, and then melt-blending, extruding, drawing and pelletizing them through a twin-screw extruder to obtain the desired flame-retardant polyamide core layer material, and drying them for standby use; The extruder temperature is 225-265°C, the drying temperature is 70-110°C, and the final moisture content is less than 600ppm; S300, adding different raw materials into the extruders of the flame retardant upper surface layer, the flame retardant polyamide core layer and the flame retardant lower surface layer respectively, and then melting and plasticizing and extruding them at a temperature of 240 to 280° C. through their respective extruders, and flowing out through a T-die; S400, using a low-pressure air knife to attach the melt to a cold drum to form a thick sheet, wherein the thickness of the thick sheet is 90 to 600 μm, and the temperature of the cold drum is 10 to 45°C; S500, immerse the thick slice in a water tank at 30-85°C for pretreatment; S600, heating the thick sheet and then performing synchronous biaxial stretching using a Bruckner magnetic suspension synchronous biaxial stretching device, wherein the stretching temperature is 145-210° C. and the stretching ratio is 2.9×2.9-4.0×4.0; S700, subjecting the stretched film to heat setting treatment, wherein the setting temperature is 170-228°C, the setting time is 1-50s, and then the film is cooled and subjected to corona post-treatment, the corona treatment power is 5-16Wmin / m², and then rolled up; S800, cutting the rolled biaxially oriented polyamide film as required to obtain the flame-retardant biaxially oriented polyamide film.

[0015] The flame-retardant biaxially oriented polyamide film provided by the present invention has the following beneficial effects: The multi-layer flame-retardant design structure has outstanding flame-retardant properties and builds three flame-retardant defense lines for the film. The flame retardant of the flame-retardant polyamide core layer is selected from different types of flame retardants, which has a multi-component synergistic effect and avoids the flame-retardant defects of a single material. The flame retardant used has good compatibility and can effectively avoid the problem of mechanical property degradation caused by large addition amount. The flame retardant is not easy to precipitate and has little effect on the mechanical properties.

[0016] In the preferred embodiment, 1,2-cyclohexanediol diglycidyl ether is selected as the molecular chain extender of the flame-retardant biaxially stretched polyamide film of the present invention. In combination with other technical features of the stretched polyamide film of the present invention, adding a small amount of 1,2-cyclohexanediol diglycidyl ether can increase the viscosity of the material, significantly improve the melt strength, and ultimately further improve the mechanical properties of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0018] Figure 1 This is a schematic diagram of the structure of a flame-retardant biaxially oriented polyamide film provided by the present invention.

[0019] Reference numerals 10. Flame retardant upper surface 20. Flame retardant polyamide core layer 30. Flame retardant lower surface DETAILED DESCRIPTION In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] The present invention provides the following flame retardant biaxially oriented polyamide film embodiments, such as Figure 1 As shown, from top to bottom, it is composed of a flame retardant upper surface layer 10, a flame retardant polyamide core layer 20 and a flame retardant lower surface layer 30. Example 1 The total thickness of the polyamide film is 15 μm; the thickness of the flame-retardant upper surface layer and the flame-retardant lower surface layer are both 2 μm; and the thickness of the flame-retardant polyamide core layer is 11 μm.

[0021] Flame retardant biaxially oriented polyamide film by mass: Flame retardant upper surface layer: including 5 parts of anti-sticking masterbatch and 95 parts of flame retardant nylon composite material; The flame retardant polyamide core layer includes 8 parts of 3-ethylenebis(ethylphosphinate)aluminum salt and 92 parts of flame retardant nylon composite material; The flame retardant lower surface layer includes 5 parts of anti-sticking masterbatch and 95 parts of flame retardant nylon composite material.

[0022] Flame retardant nylon composite material: including 80.2 parts of caprolactam, 6 parts of purified water, 12 parts of flame retardant units, 0.8 parts of glacial acetic acid, and 1 part of molecular chain extender; wherein the molecular chain extender is 1,2-cyclohexanediol diglycidyl ether.

[0023] The flame retardant unit is composed of 30 parts of active dicarboxylic acid phosphine oxide flame retardant monomer, 40 parts of polyhydroxy phosphonate and 30 parts of 9,10-dihydro-9-oxa-10-phosphaphenanthrene oxide.

[0024] The preparation method of the flame retardant nylon composite material is as follows: Add caprolactam, purified water, flame retardant unit, glacial acetic acid and molecular chain extender into a high-pressure reactor, evacuate for 60 minutes, introduce nitrogen for 20 minutes, and circulate 6 times to ensure that all components are under nitrogen protection conditions, and control the pressure in the high-pressure reactor to maintain at 0.8 MPa; Heat the autoclave to 80°C and start stirring at 90r / min for 6 hours to ensure that the mixture is completely melted and becomes a uniformly mixed fluid. The autoclave was heated to 260°C and reacted for 18 hours under this condition, and the pressure was reduced to normal pressure by venting, and the temperature was reduced to 80°C to obtain a polymer; The polymer was discharged from the casting belt, pelletized, dried at 90° C. and the moisture content was controlled to be less than 500 ppm to obtain the flame retardant nylon composite material required in this embodiment.

[0025] Anti-sticking masterbatch: by weight, it contains 82.5 parts of polyamide 6, 5 parts of lubricant, 10 parts of anti-blocking agent, 1.5 parts of antioxidant and 1 part of nucleating agent.

[0026] The lubricant is selected from stearamide; the opening agent is selected from silicon dioxide; the antioxidant is selected from antioxidant 1098 and antioxidant 168 mixed in a ratio of 2:1; and the nucleating agent is caprolactam cyclic dimer.

[0027] The preparation method of the flame-retardant biaxially oriented polyamide film of this embodiment is as follows: Step 1: Mix polyamide 6 and / or lubricant and / or anti-blocking agent and / or antioxidant and / or nucleating agent in a high-speed mixer according to a set ratio, melt blend, extrude, draw and pelletize through a twin-screw extruder to obtain the required anti-sticking masterbatch, and dry it for use. The extruder temperature is 250°C, the drying temperature is 80°C, and the moisture content of the final anti-sticking masterbatch is less than 700ppm; Step 2: Mix the flame-retardant nylon composite material and 3-ethylenebis(ethylphosphinate)aluminum salt according to the set ratio, put them into a high-speed mixer for uniform mixing to make them dispersed evenly, and then melt blend, extrude, draw and pelletize them through a twin-screw extruder to obtain the required flame-retardant polyamide core layer material, and dry them for use. The extruder temperature is 245°C, the drying temperature is 80°C, and the final moisture content is less than 550ppm; Step 3: According to the formula design requirements, different raw materials are added into the extruders of the flame retardant upper surface layer, the flame retardant polyamide core layer and the flame retardant lower surface layer respectively, and then melted and plasticized and extruded at a temperature of 260°C through their respective extruders, and flowed out through the T-die; Step 4: Use a low-pressure air knife to attach the melt to a cold drum to form a thick sheet, where the thickness of the thick sheet is 195 μm and the temperature of the cold drum is 20°C; Step 5: Immerse the thick slice in a 55°C water tank for pretreatment; Step 6: After heating the thick sheet, use Bruckner magnetic suspension synchronous biaxial stretching equipment to perform synchronous biaxial stretching, wherein the stretching temperature is 190°C and the stretching ratio is 3.1×3.5; Step 7: The stretched film is subjected to heat setting treatment, wherein the setting temperature is 210°C and the setting time is 30s, and then the film is cooled and corona treated, the corona treatment power is 9Wmin / m², and then rolled up; Step 8: The rolled biaxially oriented polyamide film is cut as required to obtain the flame-retardant biaxially oriented polyamide film having a thickness of 15 μm.

[0028] Example 2 The total thickness of the polyamide film is 12 μm; the thickness of the flame-retardant upper surface layer and the flame-retardant lower surface layer are both 1 μm; and the thickness of the flame-retardant polyamide core layer is 10 μm.

[0029] Flame retardant biaxially oriented polyamide film by mass: Flame retardant upper surface layer: including 2 parts of anti-sticking masterbatch and 98 parts of flame retardant nylon composite material; Flame retardant polyamide core layer: including 3 parts of 3-ethylenebis(ethylphosphinate) aluminum salt and 97 parts of flame retardant nylon composite material; The flame retardant lower surface layer includes 2 parts of anti-sticking masterbatch and 98 parts of flame retardant nylon composite material.

[0030] Flame retardant nylon composite material: including 88.5 parts of caprolactam, 5 parts of purified water, 6 parts of flame retardant units, 0.2 parts of glacial acetic acid, and 0.3 parts of molecular chain extender; wherein the molecular chain extender is 1,2-cyclohexanediol diglycidyl ether.

[0031] The flame retardant unit is composed of 20 parts of active dicarboxylic acid phosphine oxide flame retardant monomer, 30 parts of polyhydroxy phosphonate and 50 parts of 9,10-dihydro-9-oxa-10-phosphaphenanthrene oxide.

[0032] The preparation method of the flame retardant nylon composite material is as follows: Add caprolactam, purified water, flame retardant unit, glacial acetic acid and molecular chain extender into a high-pressure reactor, evacuate for 10 minutes, introduce nitrogen for 5 minutes, and cycle 3 times to ensure that all components are under nitrogen protection conditions, and control the pressure in the high-pressure reactor to maintain at 0.2MPa; Heat the autoclave to 60°C and start stirring at 20r / min for 1.5 hours to ensure that the mixture is completely melted and becomes a uniformly mixed fluid. The autoclave was heated to 220°C and reacted for 5 hours under this condition, then the pressure was reduced to normal pressure by venting and the temperature was lowered to 35°C to obtain a polymer; The polymer is discharged from the casting belt, pelletized, dried at 80°C and the moisture content is controlled to be less than 600ppm to obtain the desired flame retardant nylon composite material.

[0033] Anti-sticking masterbatch: by weight, it contains 91.6 parts of polyamide 6, 3 parts of lubricant, 5 parts of anti-blocking agent, 0.3 parts of antioxidant and 0.1 parts of nucleating agent.

[0034] The lubricant is selected from erucic acid amide; the opening agent is selected from talc; the antioxidant is selected from antioxidant 1010 and antioxidant 168 mixed in a ratio of 3:1; and the nucleating agent is 2,2'-methylene-bis-(4,6-di-tert-butylphenyl) phosphate sodium salt.

[0035] The preparation method of the flame-retardant biaxially oriented polyamide film of this embodiment is as follows: Step 1: Mix polyamide 6 and / or lubricant and / or anti-blocking agent and / or antioxidant and / or nucleating agent in a high-speed mixer according to a set ratio, melt blend, extrude, draw and pelletize through a twin-screw extruder to obtain the required anti-sticking masterbatch, and dry it for use. The extruder temperature is 225°C, the drying temperature is 70°C, and the moisture content of the final anti-sticking masterbatch is less than 800ppm; Step 2: Mix the flame-retardant nylon composite material and 3-ethylenebis(ethylphosphinate)aluminum salt according to the set ratio, put them into a high-speed mixer for uniform mixing to make them dispersed evenly, and then melt blend, extrude, draw and pelletize them through a twin-screw extruder to obtain the required flame-retardant polyamide core layer material, and dry them for use. The extruder temperature is 225°C, the drying temperature is 70°C, and the final moisture content is less than 600ppm; Step 3: According to the formula design requirements, different raw materials are added into the extruders of the flame retardant upper surface layer, the flame retardant polyamide core layer and the flame retardant lower surface layer respectively, and then melted and plasticized and extruded at a temperature of 245°C through their respective extruders, and flowed out through the T-die; Step 4: Use a low-pressure air knife to attach the melt to the cold drum to form a thick sheet, where the thickness of the thick sheet is 145 μm and the temperature of the cold drum is 12°C; Step 5: Immerse the thick slice in a 45°C water tank for pretreatment; Step 6: After heating the thick sheet, use Bruckner magnetic suspension synchronous biaxial stretching equipment to perform synchronous biaxial stretching, wherein the stretching temperature is 160°C and the stretching ratio is 3.0×3.0; Step 7: The stretched film is subjected to heat setting treatment, wherein the setting temperature is 195°C and the setting time is 5s, and then the film is cooled and corona treated, the corona treatment power is 6Wmin / m², and then rolled up; Step 8: The rolled biaxially oriented polyamide film is cut as required to obtain the flame-retardant biaxially oriented polyamide film, the thickness of which is 12 μm.

[0036] Example 3 The total thickness of the polyamide film is 25 μm; the thickness of the flame retardant upper surface layer and the flame retardant lower surface layer are both 2.5 μm; and the thickness of the flame retardant polyamide core layer is 20 μm.

[0037] Flame retardant biaxially oriented polyamide film by mass: Flame retardant upper surface layer: including 8 parts of anti-sticking masterbatch and 92 parts of flame retardant nylon composite material; The flame retardant polyamide core layer includes 13 parts of 3-ethylenebis(ethylphosphinate)aluminum salt and 87 parts of flame retardant nylon composite material; The flame retardant lower surface layer includes 9 parts of anti-sticking masterbatch and 91 parts of flame retardant nylon composite material.

[0038] Flame retardant nylon composite material: comprising 64.7 parts of caprolactam, 9 parts of purified water, 19 parts of flame retardant units, 2.8 parts of glacial acetic acid, and 4.5 parts of molecular chain extender; wherein the molecular chain extender is 1,2-cyclohexanediol diglycidyl ether.

[0039] The flame retardant unit is composed of 40 parts of active dicarboxylic acid phosphine oxide flame retardant monomer, 50 parts of polyhydroxy phosphonate and 10 parts of 9,10-dihydro-9-oxa-10-phosphaphenanthrene oxide.

[0040] The preparation method of the flame retardant nylon composite material is as follows: Add caprolactam, purified water, flame retardant unit, glacial acetic acid and molecular chain extender into a high-pressure reactor, evacuate for 110 minutes, introduce nitrogen for 35 minutes, and circulate 9 times to ensure that all components are under nitrogen protection conditions, and control the pressure in the high-pressure reactor to maintain at 1.2 MPa; The autoclave was heated to 90°C and stirring was started at 150 r / min. The stirring speed was kept at this condition for 9 hours to ensure that the mixture was completely melted and became a uniformly mixed fluid. The autoclave was heated to 280°C and reacted under this condition for 23 hours, then the pressure was reduced to normal pressure and the temperature was lowered to 90°C to obtain a polymer; The polymer is discharged from the casting belt, pelletized, dried at 110°C and the moisture content is controlled to be less than 500ppm to obtain the desired flame retardant nylon composite material.

[0041] Anti-sticking masterbatch: by weight, it contains 74.7 parts of polyamide 6, 9 parts of lubricant, 12 parts of anti-blocking agent, 2.5 parts of antioxidant and 1.8 parts of nucleating agent.

[0042] The lubricant is selected from erucamide and stearamide, which are mixed in a ratio of 1:2; the opening agent is selected from silicon dioxide; the antioxidant is selected from antioxidant 1010, antioxidant 168, and antioxidant SEED, which are mixed in a ratio of 3:1:1; the nucleating agent is selected from caprolactam cyclic dimer and 2,2'-methylene-bis-(4,6-di-tert-butylphenyl) phosphate sodium salt, which are mixed in a ratio of 1:1.

[0043] The preparation method of the flame-retardant biaxially oriented polyamide film of this embodiment is as follows: Step 1: Mix polyamide 6 and / or lubricant and / or anti-blocking agent and / or antioxidant and / or nucleating agent in a high-speed mixer according to a set ratio, melt blend, extrude, draw and pelletize through a twin-screw extruder to obtain the required anti-sticking masterbatch, and dry it for use. The extruder temperature is 265°C, the drying temperature is 95°C, and the moisture content of the final anti-sticking masterbatch is less than 500ppm; Step 2: Mix the flame-retardant nylon composite material and 3-ethylenebis(ethylphosphinate)aluminum salt according to the set ratio, put them into a high-speed mixer for uniform mixing to make them dispersed evenly, and then melt blend, extrude, draw and pelletize them through a twin-screw extruder to obtain the required flame-retardant polyamide core layer material, and dry them for use. The extruder temperature is 260°C, the drying temperature is 105°C, and the final moisture content is less than 450ppm; Step 3: According to the formula design requirements, different raw materials are added into the extruders of the flame retardant upper surface layer, the flame retardant polyamide core layer and the flame retardant lower surface layer respectively, and then melted and plasticized and extruded at a temperature of 270°C through their respective extruders, and flowed out through the T-die; Step 4: Use a low-pressure air knife to attach the melt to the cold drum to form a thick sheet, where the thickness of the thick sheet is 300 μm and the temperature of the cold drum is 40°C; Step 5: Immerse the thick slice in a water tank at 80°C for pretreatment; Step 6: After heating the thick sheet, use Bruckner magnetic suspension synchronous biaxial stretching equipment to perform synchronous biaxial stretching, wherein the stretching temperature is 205°C and the stretching ratio is 3.3×3.8; Step 7: The stretched film is subjected to heat setting treatment, wherein the setting temperature is 225°C and the setting time is 40s, and then the film is cooled and corona treated at a power of 15Wmin / m², and then rolled up; Step 8: The rolled biaxially oriented polyamide film is cut as required to obtain the flame-retardant biaxially oriented polyamide film having a thickness of 25 μm.

[0044] In the above examples 1, 2, and 3, the particle size D of 3-ethylenebis(ethylphosphinate)aluminum salt is 50 ≤1.2μm, particle size D 95 ≤3.0μm; Phosphorus content of 3-ethylenebis(ethylphosphinate)aluminum salt ≥23%.

[0045] Reactive dicarboxylic acid phosphine oxide flame retardant monomer refers to a substance with the following structure:

[0046] Polyhydroxyphosphonates are substances having the following structure:

[0047] In Examples 1 and 2, 9,10-dihydro-9-oxa-10-phosphaphenanthrene oxide is a substance having the following structure: ; The 9,10-dihydro-9-oxa-10-phosphaphenanthrene oxide in Example 3 refers to a substance having the following structure:

[0048] The present invention also provides the following comparative examples: Comparative Example 1 Compared with Example 1, the difference is that, the flame-retardant biaxially oriented polyamide film, calculated by weight, has a flame-retardant upper surface layer comprising 5 parts of anti-sticking masterbatch and 95 parts of polyamide 6; the flame-retardant polyamide core layer is composed of 100 parts of polyamide 6; and the flame-retardant lower surface layer comprises 5 parts of anti-sticking masterbatch and 95 parts of polyamide 6.

[0049] The preparation method is: Step 1: Mix polyamide 6 and / or lubricant and / or anti-blocking agent and / or antioxidant and / or nucleating agent in a high-speed mixer according to a set ratio, melt blend, extrude, draw and pelletize through a twin-screw extruder to obtain the required anti-sticking masterbatch, and dry it for use. The extruder temperature is 250°C, the drying temperature is 80°C, and the moisture content of the final anti-sticking masterbatch is less than 700ppm; Step 2: According to the formula design requirements, different raw materials are added into the extruders of the flame retardant upper surface layer, the flame retardant polyamide core layer and the flame retardant lower surface layer respectively, and then melted and plasticized and extruded at a temperature of 260°C through their respective extruders, and flowed out through the T-die; Step 3: Use a low-pressure air knife to attach the melt to a cold drum to form a thick sheet, where the thickness of the thick sheet is 195 μm and the temperature of the cold drum is 20°C; Step 4: Immerse the thick slice in a 55°C water tank for pretreatment; Step 5: After heating the thick sheet, use Bruckner magnetic suspension synchronous biaxial stretching equipment to perform synchronous biaxial stretching, wherein the stretching temperature is 190°C and the stretching ratio is 3.1×3.5; Step 6: The stretched film is subjected to heat setting treatment, wherein the setting temperature is 210°C and the setting time is 30s, and then the film is cooled and corona treated, the corona treatment power is 9Wmin / m², and then rolled up; Step 7: The rolled biaxially oriented polyamide film is cut as required to obtain the flame-retardant biaxially oriented polyamide film having a thickness of 15 μm.

[0050] The remaining conditions remain the same as in Example 1.

[0051] Comparative Example 2 Compared with Example 1, the difference is that the flame retardant polyamide core layer is composed of 100 parts of the flame retardant nylon composite material; The preparation method is: Step 1: Mix polyamide 6 and / or lubricant and / or anti-blocking agent and / or antioxidant and / or nucleating agent in a high-speed mixer according to a set ratio, melt blend, extrude, draw and pelletize through a twin-screw extruder to obtain the required anti-sticking masterbatch, and dry it for use. The extruder temperature is 250°C, the drying temperature is 80°C, and the moisture content of the final anti-sticking masterbatch is less than 700ppm; Step 2: According to the formula design requirements, different raw materials are added into the extruders of the flame retardant upper surface layer, the flame retardant polyamide core layer and the flame retardant lower surface layer respectively, and then melted and plasticized and extruded at a temperature of 260°C through their respective extruders, and flowed out through the T-die; Step 3: Use a low-pressure air knife to attach the melt to a cold drum to form a thick sheet, where the thickness of the thick sheet is 195 μm and the temperature of the cold drum is 20°C; Step 4: Immerse the thick slice in a 55°C water tank for pretreatment; Step 5: After heating the thick sheet, use Bruckner magnetic suspension synchronous biaxial stretching equipment to perform synchronous biaxial stretching, wherein the stretching temperature is 190°C and the stretching ratio is 3.1×3.5; Step 6: The stretched film is subjected to heat setting treatment, wherein the setting temperature is 210°C and the setting time is 30s, and then the film is cooled and corona treated, the corona treatment power is 9Wmin / m², and then rolled up; Step 7: The rolled biaxially oriented polyamide film is cut as required to obtain the flame-retardant biaxially oriented polyamide film having a thickness of 15 μm.

[0052] The remaining conditions remain the same as in Example 1.

[0053] Comparative Example 3 Compared with Example 1, the difference is that the flame retardant upper surface layer and the flame retardant lower surface layer include 5 parts of anti-sticking masterbatch and 95 parts of polyamide 6; The flame retardant polyamide core layer includes 8 parts of 3-ethylenebis(ethylphosphinate)aluminum salt and 92 parts of polyamide 6; The preparation method is: Step 1: Mix polyamide 6 and / or lubricant and / or anti-blocking agent and / or antioxidant and / or nucleating agent in a high-speed mixer according to a set ratio, melt blend, extrude, draw and pelletize through a twin-screw extruder to obtain the required anti-sticking masterbatch, and dry it for use. The extruder temperature is 250°C, the drying temperature is 80°C, and the moisture content of the final anti-sticking masterbatch is less than 700ppm; Step 2: Mix polyamide 6 and 3-ethylenebis(ethylphosphinate)aluminum salt according to the set ratio, put them into a high-speed mixer for uniform mixing to make them dispersed evenly, and then melt blend, extrude, draw and pelletize them through a twin-screw extruder to obtain the required flame-retardant polyamide core layer material, and dry them for use. The extruder temperature is 245°C, the drying temperature is 80°C, and the final moisture content is less than 550ppm; Step 3: According to the formula design requirements, different raw materials are added into the extruders of the flame retardant upper surface layer, the flame retardant polyamide core layer and the flame retardant lower surface layer respectively, and then melted and plasticized and extruded at a temperature of 260°C through their respective extruders, and flowed out through the T-die; Step 4: Use a low-pressure air knife to attach the melt to a cold drum to form a thick sheet, where the thickness of the thick sheet is 195 μm and the temperature of the cold drum is 20°C; Step 5: Immerse the thick slice in a 55°C water tank for pretreatment; Step 6: After heating the thick sheet, use Bruckner magnetic suspension synchronous biaxial stretching equipment to perform synchronous biaxial stretching, wherein the stretching temperature is 190°C and the stretching ratio is 3.1×3.5; Step 7: The stretched film is subjected to heat setting treatment, wherein the setting temperature is 210°C and the setting time is 30s, and then the film is cooled and corona treated, the corona treatment power is 9Wmin / m², and then rolled up; Step 8: The rolled biaxially oriented polyamide film is cut as required to obtain the flame-retardant biaxially oriented polyamide film having a thickness of 15 μm.

[0054] The remaining conditions remain the same as in Example 1.

[0055] Comparative Example 4 Compared with Example 1, the difference is that the flame retardant unit in the flame retardant nylon composite material is composed of an active dicarboxylic acid phosphine oxide flame retardant monomer; Among them, the active dicarboxylic acid phosphine oxide flame retardant monomer refers to a substance having the following structure:

[0056] The remaining conditions remain the same as in Example 1.

[0057] Comparative Example 5 Compared with Example 1, the difference is that the flame retardant unit in the flame retardant nylon composite material is composed of polyhydroxy phosphonate; Among them, polyhydroxyphosphonate refers to a substance having the following structure: .

[0058] The remaining conditions remain the same as in Example 1.

[0059] Comparative Example 6 Compared with Example 1, the difference is that the flame retardant unit in the flame retardant nylon composite material is composed of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-propionic acid methyl ester 10-oxide; Among them, 9,10-dihydro-9-oxa-10-phosphaphenanthrene oxide refers to a substance having the following structure: .

[0060] The remaining conditions remain the same as in Example 1.

[0061] Comparative Example 7 Compared with Example 1, the difference is that the flame retardant unit in the flame retardant nylon composite material is composed of an active dicarboxylic acid phosphine oxide flame retardant monomer and a polyhydroxy phosphonate; Among them, the active dicarboxylic acid phosphine oxide flame retardant monomer refers to a substance having the following structure:

[0062] Polyhydroxyphosphonates are substances having the following structure: .

[0063] The remaining conditions remain the same as in Example 1.

[0064] Comparative Example 8 Compared with Example 1, the difference is that the flame retardant unit in the flame retardant nylon composite material is composed of an active dicarboxylic acid phosphine oxide flame retardant monomer and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-propionic acid methyl ester 10-oxide; Among them, the active dicarboxylic acid phosphine oxide flame retardant monomer refers to a substance having the following structure: ; 9,10-dihydro-9-oxa-10-phosphaphenanthrene oxide refers to a substance having the following structure: .

[0065] The remaining conditions remain the same as in Example 1.

[0066] Comparative Example 9 Compared with Example 1, the difference is that the flame retardant unit in the flame retardant nylon composite material is composed of polyhydroxyphosphonate and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-propionic acid methyl ester 10-oxide; Among them, polyhydroxyphosphonate refers to a substance having the following structure:

[0067] 9,10-dihydro-9-oxa-10-phosphaphenanthrene oxide refers to a substance having the following structure: .

[0068] The remaining conditions remain the same as in Example 1.

[0069] Comparative Example 10 Compared with Example 1, the difference is that no flame retardant unit is added to the flame retardant nylon composite material; The flame retardant nylon composite material includes 92.2 parts of caprolactam, 6 parts of purified water, 0.8 parts of glacial acetic acid, and 1 part of a molecular chain extender; The remaining conditions remain the same as in Example 1.

[0070] Comparative Example 11 Compared with Example 1, the difference is that no molecular chain extender is added to the flame retardant nylon composite material; The flame retardant nylon composite material includes 81.2 parts of caprolactam, 6 parts of purified water, 12 parts of flame retardant units, and 0.8 parts of glacial acetic acid; The remaining conditions remain the same as in Example 1.

[0071] The present invention tests the relevant performances of the above-mentioned embodiments and comparative examples, and the specific result data are shown in Table 1: Table 1

[0072] In Table 1: (1) Flame retardant performance test: The test is carried out in accordance with the requirements of ISO 9773 "Plastics-Determination of burning behavior of thin f1exible vertical specimens in contact with a small-flameignition source". The flame retardant levels are represented by VTM-0, VTM-1, and VTM-2 from high to low, while × indicates that the flame retardant level does not reach VTM-2, and □ indicates that the flame retardant level is between VTM-2 and VTM-1.

[0073] (2) Tensile strength performance test: The test shall be carried out in accordance with the requirements of GB / T 1040.3 "Determination of tensile properties of plastics (Part 3: Test conditions for films and sheets)".

[0074] By comparing Example 1 and Comparative Examples 1-3 in the above table, it can be seen that by replacing all or any one of the flame-retardant nylon composite materials in the upper surface layer, the flame-retardant polyamide core layer and the lower surface layer with the existing polyamide 6, the flame retardant properties and tensile strength of the polyamide film are reduced.

[0075] It can be seen from Example 1 and Comparative Examples 4-10 that the flame retardant unit prepared by synergistically using an active dicarboxylic acid phosphine oxide flame retardant monomer, a polyhydroxy phosphonate and 9,10-dihydro-9-oxa-10-phosphaphenanthrene oxide in the technical scheme of the present invention can significantly improve the flame retardant properties and tensile strength of the polyamide film.

[0076] It can be seen from Example 1 and Comparative Example 11 that the use of the molecular chain extender of the present invention plays a key role in improving the biaxial tensile strength of the polyamide film. In particular, the use of 1,2-cyclohexanediol diglycidyl ether as a molecular chain extender in the present invention, combined with other technical features of the present invention, has the effect of increasing the viscosity of the material with a small amount of addition, and can significantly improve the melt strength, ultimately achieving the effect of improving the mechanical properties of the material.

[0077] In summary, it can be seen that the multi-layer flame retardant design structure of the film prepared by the present invention has outstanding flame retardant properties, and builds three flame retardant defense lines for the film; and the flame retardant of the flame retardant polyamide core layer of the substrate film is selected from different types of flame retardants, which has a multi-component synergistic effect and avoids the flame retardant defects of a single material; the flame retardant biaxially stretched polyamide film prepared by the present invention is compared with the biaxially stretched polyamide film produced by the traditional method. The functional layers of the flame retardant biaxially stretched polyamide film produced by the present invention cooperate and coordinate with each other to form an indivisible organic whole, which not only has outstanding flame retardant properties, but also has excellent tensile strength, which can meet the needs of the lithium ion battery packaging, electronic product packaging and other markets.

[0078] In addition, the film prepared by the present invention has wide applications and strong applicability, and its production process is simple, easy to process, high production efficiency, and easy to realize industrial production; the film product prepared by the present invention has a delicate appearance, no granularity, and does not affect transparency.

[0079] Preferably, the flame retardant is added through a polymerization reaction, which has the characteristics of good flame retardant effect and less flame retardant components added, and the flame retardant units used are not easy to precipitate and have little effect on mechanical properties. Compared with conventional flame retardants, this flame retardant material has good compatibility and can well avoid the problem of decreased mechanical properties caused by large addition amounts.

[0080] At the same time, compared with polyamide films using conventional halogen flame retardants, which produce a large amount of corrosive smoke and toxic gases during combustion, the raw materials in the polyamide film provided by the present invention will not only pollute the environment, but also will not threaten the safety of life and property. It has significant social significance.

[0081] Although the terms such as upper surface layer, lower surface layer, and flame retardant polyamide core layer are used more frequently in this article, the possibility of using other terms is not excluded. These terms are used only to more conveniently describe and explain the essence of the present invention; interpreting them as any additional limitation is contrary to the spirit of the present invention.

[0082] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A flame-retardant biaxially oriented polyamide film, characterized in that: The film is composed of a flame retardant upper surface layer, a flame retardant polyamide core layer and a flame retardant lower surface layer from top to bottom; By mass: The flame retardant upper surface layer comprises 1 to 10 parts of anti-sticking masterbatch and 90 to 99 parts of flame retardant nylon composite material; The flame retardant polyamide core layer comprises 1 to 15 parts of 3-ethylenebis(ethylphosphinate) aluminum salt and 85 to 99 parts of a flame retardant nylon composite material; The flame retardant lower surface layer comprises 1 to 10 parts of anti-sticking masterbatch and 90 to 99 parts of flame retardant nylon composite material; The flame retardant nylon composite material is polymerized by caprolactam, purified water, flame retardant unit, glacial acetic acid and molecular chain extender in a mass ratio of 62-89.8:5-10:5-20:0.1-3:0.1-5.

2. The flame-retardant biaxially oriented polyamide film according to claim 1, characterized in that: The flame retardant unit is prepared by compounding an active dicarboxylic acid phosphine oxide flame retardant monomer, polyhydroxyphosphonate and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-propionic acid methyl ester 10-oxide in a mass ratio of 20-40:30-50:10-50.

3. The flame-retardant biaxially oriented polyamide film according to claim 1, characterized in that: The polymerization of flame retardant nylon composites includes the following steps: Add caprolactam, purified water, flame retardant unit, glacial acetic acid and molecular chain extender into a high-pressure reactor, evacuate for 10 to 120 minutes, introduce nitrogen for 5 to 40 minutes, and circulate 3 to 10 times to ensure that each component is under nitrogen protection conditions, and control the pressure in the high-pressure reactor to maintain at 0.1 to 1.5 MPa; The high-pressure reactor is heated to 50-100°C, and stirring is started at the same time. The stirring speed is controlled at 20-150r / min, and under this condition, the mixture is stirred to be completely melted and become a uniformly mixed fluid; The high-pressure reactor is heated to 210-290°C and reacted under this condition for 2-24 hours, and the pressure is reduced to normal pressure by venting, and the temperature is reduced to 30-100°C to obtain a polymer; The polymer is discharged through the casting belt pelletizing, dried at 80-120° C. and the moisture content is controlled to be less than 600 ppm, thereby obtaining the desired flame retardant nylon composite material.

4. The flame-retardant biaxially oriented polyamide film according to claim 2, characterized in that: The dicarboxylic acid phosphine oxide flame retardant monomer is a substance comprising the following structure: ; The polyhydroxyphosphonate is a substance comprising the following structure: ; The 9,10-dihydro-9-oxa-10-phosphaphenanthrene oxide is a substance comprising the following structure: or .

5. The flame-retardant biaxially oriented polyamide film according to claim 1, characterized in that: The particle size D of the aluminum salt of 3-ethylenebis(ethylphosphinate) 50 ≤1.2μm, particle size D 95 ≤3.0μm, phosphorus content of aluminum salt ≥23%.

6. The flame-retardant biaxially oriented polyamide film according to claim 1, characterized in that: The anti-sticking masterbatch is composed of polyamide 6 and / or lubricant and / or opening agent and / or antioxidant and / or nucleating agent.

7. The flame-retardant biaxially oriented polyamide film according to claim 1, characterized in that: The anti-sticking masterbatch is composed of 70-91.6 parts of polyamide 6, 3-10 parts of lubricant, 5-15 parts of anti-blocking agent, 0.3-3 parts of antioxidant and 0.1-2 parts of nucleating agent by weight.

8. The flame-retardant biaxially oriented polyamide film according to claim 1, characterized in that: The lubricant is selected from any one of oleamide, erucic acid amide, ethylene bislauramide, stearamide, silicone powder, ethylene bisoleamide, ethylene bisstearamide, or a mixture of at least two of them in any proportion; The opening agent is selected from any one of silicone resin, magnesium carbonate, aluminum oxide, talc, silicon dioxide, calcium carbonate, titanium dioxide, kaolin, barium carbonate, diatomaceous earth, or a mixture of at least two of them in any proportion; The antioxidant is selected from any one of antioxidant 1010, antioxidant 1098, antioxidant 168, antioxidant SEED, and antioxidant DNP, or a mixture of at least two of them in any proportion; The nucleating agent is selected from any one of caprolactam cyclic dimer and 2,2′-methylene-bis-(4,6-di-tert-butylphenyl) phosphate sodium salt or a mixture of at least two of them in any proportion; The molecular chain extender is 1,2-cyclohexanediol diglycidyl ether.

9. The flame-retardant biaxially oriented polyamide film according to claim 1, characterized in that: The thickness of the polyamide film is 10 to 50 μm; The thickness of the flame retardant upper surface layer and the flame retardant lower surface layer are both 1-4 μm; the thickness of the flame retardant polyamide core layer is 2-48 μm.

10. A method for preparing the flame-retardant biaxially oriented polyamide film according to any one of claims 1 to 9, comprising the following steps: S100, polyamide 6 and / or lubricant and / or opening agent and / or antioxidant and / or nucleating agent are mixed in a high-speed mixer according to a set ratio, melt blended, extruded, stretched and pelletized by a twin-screw extruder to obtain the desired anti-sticking masterbatch, and dried for use; Among them, the extruder temperature is 225 ~ 275 ℃, the drying temperature is 70 ~ 100 ℃, and the moisture content of the final anti-sticking masterbatch is less than 800ppm; S200, mixing the flame-retardant nylon composite material and 3-ethylenebis(ethylphosphinate)aluminum salt according to a set ratio, and putting them into a high-speed mixer for uniform mixing to make them dispersed evenly, and then melt-blending, extruding, drawing and pelletizing them through a twin-screw extruder to obtain the desired flame-retardant polyamide core layer material, and drying them for standby use; The extruder temperature is 225-265°C, the drying temperature is 70-110°C, and the final moisture content is less than 600ppm; S300, adding different raw materials into the extruders of the flame retardant upper surface layer, the flame retardant polyamide core layer and the flame retardant lower surface layer respectively, and then melting and plasticizing and extruding them at a temperature of 240 to 280° C. through their respective extruders, and flowing out through a T-die; S400, using a low-pressure air knife to attach the melt to a cold drum to form a thick sheet, wherein the thickness of the thick sheet is 90 to 600 μm, and the temperature of the cold drum is 10 to 45°C; S500, immerse the thick slice in a water tank at 30-85°C for pretreatment; S600, heating the thick sheet and then performing synchronous biaxial stretching using a Bruckner magnetic suspension synchronous biaxial stretching device, wherein the stretching temperature is 145-210° C. and the stretching ratio is 2.9×2.9-4.0×4.0; S700, subjecting the stretched film to heat setting treatment, wherein the setting temperature is 170-228°C, the setting time is 1-50s, and then the film is cooled and subjected to corona post-treatment, the corona treatment power is 5-16Wmin / m², and then rolled up; S800, cutting the rolled biaxially oriented polyamide film as required to obtain the flame-retardant biaxially oriented polyamide film.

Citation Information

Patent Citations

  • Toughened biaxially oriented polyamide film and preparation method thereof

    CN112480659A

  • Flame-retardant polyamide composite material as well as preparation method and application thereof

    CN112646367A

  • Flame-retardant extinction polyamide film and preparation method thereof

    CN116100895A